Anisotropic compressive response of Stone–Thrower–Wales defects in graphene: A molecular dynamics study. (13th September 2016) - Rajasekaran, G; Parashar, Avinash
Abstract: The mechanical properties of graphene sheet can be tailored with the help of topological defects. In this research article, the effects of Stone–Thrower–Wales (STW) defects on the mechanical properties of graphene sheet was investigated with the help of molecular dynamics based simulations. Authors has made an attempt to analyse the stress field developed in and around the vicinity of defect due to bond reorientation and further systematic evaluation has been carried out to study the effect of these stress fields against the applied axial compressive load. The results obtained with the pristine graphene were made to compare with the available open literature and the results were reported to be in good agreement with theoretical and experimental data. It was predicted that graphene with STW defect cannot able to bear compressive strength in zigzag direction, whereas on the other hand it was predicted that graphene sheet containing STW defect can bear higher compressive load in armchair direction, which shows an anisotropic response of STW defects in graphene. From the obtained results it can be observed that orientation of STW defects and the loading direction plays an important role to alter the strength of graphene under axial compression.